Fetomaternal Outcomes in Placenta Previa with and without Coverage of a Uterine Scar in a Tertiary Hospital in Chattogram, Bangladesh (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2026)
Background: Placenta Previa (PP) is a significant cause of maternal and fetal morbidity and mortality, especially in patients with scared uterus. This study aimed to compare the maternal and neonatal outcomes of PP with and without coverage of a uterine scar in a tertiary hospital in Chattogram, Bangladesh. Materials and methods: A prospective observational study was conducted from January 2024 to June 2024 in Chittagong Medical College Hospital. Consecutively admitted 38 singleton pregnancies with PP with a history of Cesarean Section (CS) or myomectomy were included and divided into two groups: the PP with coverage of a uterine scar group (PPCS group) and the PP without coverage of a uterine group (Non-PPCS group). Maternal and neonatal outcomes between two groups were compared by statistical methods. Results: There were 38 patients with with PP on scared uterus and were further classified into two groups: PPCS (n=23) and Non-PPCS (n=18). Both the groups were comparable in terms of their baseline sociodemographic and clinical characteristics. Placenta accreta spectrum was (95.7% vs. 20%.0, p